CONTRADIÇÃO E RESISTÊNCIA NO DISCURSO SOBRE AS PROSTITUTAS JUDIAS-POLACAS - BALDISSERA, RAQUEL (2023)
This research is inscribed in discourse analysis, proposed by Michel Pêcheux and constantly rethought by Eni Orlandi and researchers who share with her the theory and advances and resumptions that scientific knowledge demands. We take as corpus the work "Ball of masks: Jewish Women and Prostitution: Polish women and their associations of Mutual Aid", by Beatriz Kushnir (1996), which we mean as a place of memory, by presenting the historical, the cultural, the discursive by symbolic relations, which does not circulate in social formation because it was silenced by the Jewish-Christian community. The analytical analysis focuses on the Polish-Jewish prostitutes who came to Brazil, fleeing Europe in 1867, due to the conditions of misery in which they lived. We mobilize, therefore, theoretical conceptions of Discourse Analysis (AD), which support the analysis of the corpus in which the text is a material place of discourse. In this perspective, the text is the unit of analysis and forwards to different discourses, considering that the senses can always be others (ORLANDI, 1999) and are constituted by the conditions of production and by subjects questioned by ideology and crossed by the unconscious. Discursive materialities are constituted by memories and pre-constructed materialities (PÊCHEUX, [1975] 1997a, p. 162) as "something speaks" (ça parle) always "before elsewhere, independently" (griffins of the author) and return from subjects always divided, inscribed in discursive formations, which have shifting borders (ORLANDI, 2002). In the corpus under analysis, religious and cultural discourse crosses and anchors the exclusion of The Jewish-Polish, practiced mainly by Jewish-men, considering that the legitimacy of practices and discourses was in line with the structural patriarchy in operation. With this, the contradiction is established, that is, the subjects remain in the same DF, but occupy different positions-subject. The Jewish-Polish prostitutes even enrolled in the same discursive formation of The Jews-men, resist, and seek to promote the help, building cemeteries for the excluded, thus denying the social, religious, and cultural division that permeates the discourse. These are women born in Eastern Europe, almost illiterate and without a dowry, which made marriage difficult, enabling pimps, often Jews, to turn them into prostitutes. The question to be answered is: How do discourses and memories about women return and legitimize the exclusion of Jewish-Polish prostitutes practiced by Jewish subjects? The general objective for this dissertation is to verify by the analysis of SDs (discursive sequences) cut from the work of Kushnir (1996), how Jewish prostitutes are imaginatively represented, analyzing, and putting on hold the discursive processes and exclusion mechanisms that contribute to the construction of this discourse. The research allows us to conclude that in the discourse on Jewish-Polish prostitutes, memories of an ever-present patriarchy that legitimizes the exclusion and silencing of women, not only of prostitutes, are repeated.